International specialization and the return to capital - Cátia Batista; Jacques Potin (Institute for the Study of Labor (IZA), 2010)
How does factor accumulation affect the pattern of international specialization and returns to capital? We provide a new integrated treatment to this question using a panel of 44 developing and developed countries over the period 1976-2000. We confirm the Heckscher-Ohlin prediction that, with sufficient differences in country endowments, there is no factor price equalization and countries specialize in different subsets of goods. Innovatively, we obtain the returns to capital implied by this model: these are consistent with the Lucas paradox, which we explain after accounting for cross-country differences in the cost of capital goods. We also find that, along their development path, countries have often experienced structural change in the form of intra-industry specialization. Our findings are consistent with Ventura's hypothesis that growth can be promoted in this way through beating the curse of diminishing returns - indeed we find no decrease in the return to capital at any given capital-labor ratio despite capital accumulation by most countries within a cone of diversification.
Keywords: F11; F21; O40; 330; Economic growth and international trade; Heckscher-Ohlin; multiple cones of diversification; marginal product of capital; return to capital; Lucas paradox; specialization; Direktinvestition; Internationale Arbeitsteilung; Faktorproportionentheorem; Kapitalertrag; Panel; Schätzung; Welt